Short Communication: A comparative study of phenotypes and starch production in sago palm (Metroxylon sagu) growing naturally in temporarily inundated and non inundated areas of South Sorong, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yater T, Tubur HW, Meliala C, Abbas B. 2019. Short Communication:  A comparative study of phenotypes and starch production in sago palm (Metroxylon sagu) growing naturally in temporarily inundated and non-inundated areas of South Sorong, Indonesia. Biodiversitas 20:  1121-1126. Sago palm forests and sago palm semi cultivation are generally spread in swampy areas, seasonally inundated areas and non-inundated areas. The objectives of this study are to determine and compare the phenotypes of and starch production by sago palms growing naturally in the temporarily inundated areas (TIA type) and non-inundated areas (WIA type) in South Sorong District, West Papua Province, Indonesia. Sago palms of both habitats were found to be the same variety based on analysis of vernacular names and general characteristics. Comparison of morphological characters related to starch production of TIA and WIA types showed that there were no significant differences between the two studied types. The distribution of starch along the sago trunk was observed to be uneven, higher starch accumulation was found in the middle part of the trunk which was significantly different from the lower and upper parts of the trunk.
Keywords: inundated areas; phenotypes; production; sago palm; South Sorong